Antibacterial activity of ashitaba leaf extract against Streptococcus pneumoniae - Hutabarat, Tommy Daniel Patar P.; Suandy, Suandy; Natali, Oliviti; Djuang, Michelle Hendriani; Akbar, Khainir; Oentari, Widyaningsih; Putri, Riri Rizan; Dalimunthe, Siti Aisyah (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Infection by Streptococcus pneumoniae represents a significant global health concern, necessitating the exploration of novel antimicrobial agents, particularly in light of escalating antibiotic resistance. This study aimed to identify the phytochemical constituents and to evaluate the antibacterial activity of an ethanol extract of Ashitaba leaves (Angelica keiskei) against S. pneumoniae. This experimental study employed a post-only control group design. Extraction was performed using ethanol via maceration, followed by qualitative phytochemical screening. Antibacterial activity was assessed using the disc diffusion method at concentrations of 50, 100, and 150 mg/mL, with ciprofloxacin as a positive control. Inhibition zone data were analysed using non-parametric statistical tests. Phytochemical screening indicated the presence of flavonoids, alkaloids, saponins, tannins, glycosides, and steroids/triterpenoids. The extract demonstrated antibacterial activity with mean inhibition zones of 16.57 mm at 50 mg/mL, 26.23 mm at 100 mg/mL, and 29.87 mm at 150 mg/mL. Statistical analysis revealed no significant difference in inhibition zones among the three extract concentrations, whereas all concentrations differed significantly from the positive control, ciprofloxacin (53.67 mm). It is concluded that the ethanol extract of Ashitaba leaves contains diverse bioactive compounds and exhibits significant in vitro antibacterial activity against S. pneumoniae, although its efficacy remains inferior to the synthetic antibiotic ciprofloxacin.